Dorsal and ventral stimuli in sandwich‐like microenvironments. Effect on cell differentiation. Issue 11 (27th June 2013) - Ballester‐Beltrán, José; Lebourg, Myriam; Salmerón‐Sánchez, Manuel
ABSTRACT While most of the in vivo extracellular matrices are 3D, most of the in vitro cultures are 2D—where only ventral adhesion is permitted—thus modifying cell behavior as a way to self‐adaptation to this unnatural environment. We hypothesize that the excitation of dorsal receptors in cells already attached on a 2D surface (sandwich culture) could cover the gap between 2D and 3D cell–material interactions and result in a more physiological cell behavior. In this study we investigate the role of dorsal stimulation on myoblast differentiation within different poly(L‐lactic acid) (PLLA) sandwich‐like microenvironments, including plain material and aligned fibers. Enhanced cell differentiation levels were found for cells cultured with dorsal fibronectin‐coated films. Seeking to understand the underlying mechanisms, experiments were carried out with (i) different types of dorsal stimuli (FN, albumin, FN after blocking the RGD integrin‐binding site and activating dorsal cell integrin receptors), (ii) in the presence of an inhibitor of cell contractility, and (iii) increasing the frequency of culture medium changes to assess the effect of paracrine factors. Furthermore, FAK and integrin expressions, determined by Western blotting, revealed differences between cell sandwiches and 2D controls. Results show a stimuli‐dependent response to dorsal excitation, proving that integrin outside‐in signaling is involved in the enhanced cell differentiation. Due to their easiness and versatility, these sandwich‐like systems are excellent candidates to get deeper insights into the study of 3D cell behavior and to direct cell fate within multilayer constructs. Biotechnol. Bioeng. 2013;110: 3048–3058. © 2013 Wiley Periodicals, Inc.